Regional concept for the development of science education in the secondary school of Samarkand region - Yunusov Kh.B (Universitas Muhammadiyah Sidoarjo, 2019)
This concept creates favorable conditions for the development and implementation of mechanisms for the development of school science education in Samarkand region of the Republic of Uzbekistan taking into account the programs developed and implemented at the current stage of development of the region. This approach allows us to strengthen the position with staffing for teachers (biology, chemistry, physics, mathematics) of the secondary school and to achieve the integration of rural and city schools to create a single educational space. It will increase the motivation of students and activate the work of teachers of biology, chemistry, physics, and mathematics, which will lead to the full formation of the initial stage of professional orientation in the natural sciences